(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2024)
Through the experience of an extension exhibition on the fruit and vegetable belt of General Pueyrredon, the article reflects on the power of images and photography as discursive tools that allow workers to show their experiences from their own perspectives, questioning the stereotypes that circulate about them. Secondly, it explores about what these images show: inequalities in which gender and migratory origin become a central cleavage in the experiences of historically subalternised subjects, but also situations in which they have the autonomy and agency to question these inequalities.